2001
DOI: 10.1017/s1360641701002520
|View full text |Cite
|
Sign up to set email alerts
|

Using North American Instruments with British Samples: Norms for the Revised Children's Manifest Anxiety Scale in the UK

Abstract: The Revised Children's Manifest Anxiety Scale is a widely used assessment tool, but it is questionable whether the North American norms are applicable to a British population. The scale was administered to 575 English children aged 8–12 years. Means were computed by age and gender and compared to the published North American norms. English males reported less anxiety than American males in most age groups, while 8-year-old English girls reported less anxiety than 8-year-old American girls. The language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…5,7 Our research indicates that children presenting to their primary care physicians with MUPS fail to manifest large increments in anxiety, not only relative to control patients from the same clinics but also relative to a cross-section of age peers in the United States and the United Kingdom. 23 Our MUPS patients actually scored slightly lower on the RCMAS than did a cross-section of American children, while scoring slightly higher than the British children, although, again, neither difference was statistically significant, P s > .10.…”
Section: Discussioncontrasting
confidence: 48%
“…5,7 Our research indicates that children presenting to their primary care physicians with MUPS fail to manifest large increments in anxiety, not only relative to control patients from the same clinics but also relative to a cross-section of age peers in the United States and the United Kingdom. 23 Our MUPS patients actually scored slightly lower on the RCMAS than did a cross-section of American children, while scoring slightly higher than the British children, although, again, neither difference was statistically significant, P s > .10.…”
Section: Discussioncontrasting
confidence: 48%
“…The children were asked to rate their own appetites, comparing them with those of their best friend and their same and opposite sex siblings, and their carer (usually their mother) was asked independently to make the same ratings in respect of their child. Selfesteem, anxiety and depression symptoms were assessed directly using the child as the informant with the Self-perception Profile for Children (Harter, 1982;Hoare, Elton, Greer, & Kerley, 1993), the Revised Children's Manifest Anxiety Scale (Mertin, Dibnah, Crosbie, & Bulkley, 2001;Reynolds & Richmond, 1978) and the Mood and Feelings Questionnaire (Kent, Vostanis, & Feehan, 1997). In addition the child's carer (usually the mother) was asked to complete the parent's form of the Mood and Feelings Questionnaire (MFQ-P; the child's version is the MFQ-C).…”
Section: Methodsmentioning
confidence: 99%
“…The Total Anxiety score is converted to a T-score with a mean of 50 and standard deviation of 10. Mertin, Dibnah, Crosbie and Bulkley (2001) found that British children scored significantly lower than the American normative sample. They provided norms for children aged 8–12 years, reporting the mean for 8-year-old girls as 13.69 ( SD = 6.53) and boys as 11.13 ( SD = 5.62), and recommended administering the measure as a structured interview.…”
Section: Methodsmentioning
confidence: 97%